Perbandingan Random Forest dan SVM pada Analisis Sentimen Reformasi Pendidikan - Nur Hayati; Nova Tri Romadloni (STMIK PPKIA Tarakanita Rahmawati, 2026)
This study aims to compare the performance of the Random Forest and Support Vector Machine (SVM) algorithms in conducting sentiment analysis on YouTube comments related to education reform in Indonesia. The dataset used in this study consisted of 981 comments collected from the YouTube platform, and randomly labeled with two categories: